Management of quality and innovation in a changing business environment : future challenges and opportunities - Terziovski, Milé (Journal of manufacutring technology management, 2004)
The focus on organisational excellence in the first instance must be excellence, defined by The Australian Concise Oxford Dictionary as "surpassing merit; thing in which persons etc. excel," where to excel is to "be superior". To be excellent one must exceed the existing, to "do more than is warranted by, go beyond the limit set by ... surpass." This paper examines the limits to organisational excellence by investigating the knowledge base behind the perceptions, values and beliefs that have developed both within business and business education over the last 100 years and provides supporting.